The president of the O'Connor 50+ Club displayinh embroidery. - Brzycki, Sharna (2014)
Marilyn, the president of the O'Connor 50+ Club of Witless Bay and Bay Bulls, displays an embroidery piece made by her mother years ago. During "Craft Night", a weekly event held by the group.